The Effect Of Digitization Transformation On Financial Performance: A Case Study Of Banking Companies In Indonesia - Silva Nurbaiti Pertiwi; Jamaludin Jamaludin; Ignatius Henry Wicaksono; Henny Setyo Lestari; Farah Margaretha Leon (Publikasi Indonesia, 2023)
This study aimed to analysis the influence of digital transformation, bank size, CAR, loan & liquidity ratio, NPL, inflation and GDP growth to ROA and ROE with LLP and deposit growth as a control variable. The results of hypothesis testing from this study show that digital transformation, CAR, NPL, inflation, GDP growth and deposit growth have a significant effect on ROA. While bank size, loan ratio, liquidity ratio and LLP do not have a significant effect on ROA. As for the second model shows that digital transformation, bank size, NPL, inflation, GDP growth and deposit growth have a significant effect on ROE. While the CAR, loan ratio, liquidity ratio and LLP do not have a significant effect on ROE.